TRANSFORMATION OF SAFETY CULTURE: THE INFLUENCE OF THE WORK ENVIRONMENT ON THE IMPROVEMENT OF OSH KNOWLEDGE - Triwati, Ika; Jamaluddin, Jamaluddin; Purnamawati, Purnamawati (Jurnal Vokasi Keteknikan, 2025)
Occupational Safety and Health (OHS) is an important factor in the construction industry to reduce the risk of accidents and improve worker welfare. This study aims to analyze the effectiveness of the work environment approach in increasing K3 knowledge in construction industry workers. The research design used is One Group Pretest-Posttest Design involving 30 workers. The research process began with a pretest to measure the level of initial knowledge of workers, followed by filling out a questionnaire using the Likert 4 scale to determine the response of workers to the work environment approach. Furthermore, interventions were carried out in the form of training and improvement of the work environment, then ended with a posttest to measure the improvement of K3 knowledge after the intervention. The results showed a significant increase in the average score of workers' knowledge from 62.83 in the pretest to 85.17 in the posttest. This increase shows that the work environment-based approach is effective in increasing workers' awareness and understanding of OSH. The implications of this study emphasize the importance of implementing work environment-based strategies in improving safety culture in the construction industry. Companies are advised to implement a similar approach on an ongoing basis to improve worker safety and productivity.